1998
DOI: 10.1093/hmg/7.11.1753
|View full text |Cite
|
Sign up to set email alerts
|

ClC-1 Chloride Channel Mutations in Myotonia Congenita: Variable Penetrance of Mutations Shifting the Voltage Dependence

Abstract: Mutations in the ClC-1 muscle chloride channel cause either recessive or dominant myotonia congenita. Using a systematic screening procedure, we have now identified four novel missense mutations in dominant (V286A, F307S) and recessive myotonia (V236L, G285E), and have analysed the effect of these and other recently described mutations (A313T, I556N) on channel properties in the Xenopus oocyte expression system. Mutations V286A, F307S and A313T displayed a 'classical' dominant phenotype: their voltage dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 32 publications
9
115
0
1
Order By: Relevance
“…For instance, the F307S mutation was initially found in a dominant family, and electrophysiological characterization supported the dominant nature of the mutation. 14 However, the same mutation has subsequently been found the recessive families. 3 It is quite possible that allelic variation in favor for the mutation is recognized as a dominant phenotype, whereas a shift to the wild-type allele leads to recessive inheritance.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…For instance, the F307S mutation was initially found in a dominant family, and electrophysiological characterization supported the dominant nature of the mutation. 14 However, the same mutation has subsequently been found the recessive families. 3 It is quite possible that allelic variation in favor for the mutation is recognized as a dominant phenotype, whereas a shift to the wild-type allele leads to recessive inheritance.…”
Section: Discussionmentioning
confidence: 73%
“…16 In summary, genomic DNA from the probands was extracted according to standard methods and all 23 exons of CLCN1 were amplified by polymerase chain reaction (PCR) followed by sequencing using intronic primers as described by Kubisch et al 14 Identified mutations were subsequently confirmed in a new PCR and sequencing reaction. The CLCN1 sequence from the two probands, who also volunteered for cDNA analysis, did not show any differences in the primer sites for mRNA analysis.…”
Section: Human Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the mutations are semidominant (i.e., they are found in recessive as well as dominant pedigrees) (Table 1; Fig. 2) and in some of these cases it has been shown that the shift of the activation curve is either not very big [Kubisch et al, 1998;Zhang et al, 2000a] or is mainly produced by an effect on the single protopore gates [Saviane et al, 1999]. Since the two protopore gates are almost independent of each other (at least once the common gate is open) it is not expected that a modification of one of them has a dominant effect on the whole complex.…”
Section: Significancementioning
confidence: 99%
“…Based on these findings, it is nant mutations. 1,12,14,15,[23][24][25] Furthermore, heterozygotes for the CLCN1 mutation can have a broad phenotypic spectrum, even between heterozygous members of the same family. They can be asymptomatic with mild myotonia revealed only by physical examination in detail.…”
Section: Discussionmentioning
confidence: 99%